EVALUASI ATAS OPTIMALISASI PAJAK PENGHASILAN YANG DIPOTONG DAN DIPUNGUT - Ary Wibowo (JBT (JURNAL BISNIS dan TEKNOLOGI), 2022)
As a major contributor to the revenue in the country, pursued in an optimal taxation revenue through reforms in the field of regulation and legislation, this has resulted in decreased tax revenues for short-term. In addition to tariff reduction, the global crisis is also one factor of the decline in tax revenues. The purpose of reform is to optimize the tax rules on income tax.